Delimiting the "Balaton Riviera" tourist destination by using network analysis - Madarász, Eszter; Papp, Zsófia (Hungarian Geographical Bulletin, 2013)
Recently the recognition of the role, potential within, and analysis of networks has been increasing in business and academic areasl. Network analysis has also been applied widely in tourism, as numerous researchers are studying connections among elements of tourism, with the main focus on destinations, cooperation and the efficiency of cooperation among players of destination management organisations. The methodology applied in those researches has reinvented social network analyis, which has noteable historical roots in mathematics, sociology, and anthropology. As identified in the title, the subject of this study aims to delimit destinations which have been researched in a micro-region (Felsőörs, Lovas, Paloznak, Alsóörs, Csopak) of a Balaton Region, Hungary’s number one tourist destination as well as the local destination management organisation “Balaton Riviera”. Analyzing the data we can conclude that our hypothesis posed at the beginning of the research is verified, namely in the case of this micro region the connections among the actors mark the boundaries of the destination. For the time being, the scope of this research is limited to pilot research only, but thanks to sophisticated methodology and soft wares it can be upscaled to manage huge databases as well, and therefore the results achieved herein can be tested elsewhere and generalized.